Buddhist Mahâyâna texts - Aśvaghoṣa ca. 1./2. Jh.; Cowell, Edward B.; Müller, Friedrich Max; Takakusu, Junjirō (Sacred books of the East, 1894)
pt. I. The Buddha-karita of Asvaghosha, translated from the Sanskrit by E.B. Cowell.--pt. II. The larger Sukhâvatî-vyûtha, the smaller Sukhâvatî-vyûha, the Vagrakkhedikâ, the larger Pragñâ-pâra-mitâ-hridaya-sûtra, the smaller Pragñâ-pâramitâ-hridaya-sûtra, translated by F. Max Müller. The Amitâyur-dhyâna-sûtra, translated by J. Takakusu.